A theoretical grounding of teacher leadership. Issue 2 (10th March 2020) - Nerlino, Erin
Abstract : Purpose: This paper identifies two conceptualizations of teacher leadership – constructivist leadership theory and sociocultural theory. Using aspects of the conceptualizations, this paper provides direction for future study into and implementation of teacher leadership. Design/methodology/approach: This paper draws from both review and empirical literature that references constructivist leadership theory and sociocultural theory or that describes aspects of the aforementioned theories in relation to teacher leadership. Findings: Findings reveal that both constructivist leadership theory and sociocultural theory provide insight into the past lukewarm success of teacher leadership implementation and guidance for future efforts in teacher leadership. Such efforts include reconceptualizing leadership in schools, redesigning development opportunities for teachers based on the link between leading and learning, capitalizing on collaboration between universities and schools, focusing on the mentorship of new teachers and developing teacher leadership in relation to well-studied local school cultures. Originality/value: The literature reviews of York-Barr and Duke (2004) and Wenner and Campbell (2017) regarding teacher leadership describe the field as largely atheoretical. This paper provides a theoretical grounding for teacher leadership in constructivist leadership theory and sociocultural theory and derives direction for future work around teacher leadership from a combination of these theories.